A Review of Cash Holding and Corporate Governance Mechanisms in Transition Economies - Nhan, Do Thi Thanh (International Review of Management and Marketing, 2017)
In this paper, the main purpose is to present a review of the relationship between cash holding and corporate governance mechanims. To achieve it, the study reviews the related papers to discover the connections between some internal and external corporate governance mechanims which impact on the cash reserve. The paper finds out the ownership struture, board structure and regulations influence on the cash holding level in transition economies. Based on the review, the paper developes the hypotheseses, conceptual framework and methodology. The paper analyses the current studies to sugguest the furture research for developing a model. Keywords: Cash Holding, Corporate Governance Mechanisms, Transition Economies JEL Classifications: G30, G32, P2